Social contract as a tool of state social protection - N. S. Sergienko (Вестник университета, 2025)
The article considers the programme of social protection of the population – the social contract (hereinafter referred to as SC). Its development and implementation in the Russian Federation has allowed to bring forms of support for citizens and fight against poverty to a new level. The author considers the main results of the project implementation which has made it possible to change the approach in the fight against poverty to a stimulating mechanism of self-sufficiency. The experience of individual foreign countries described and analysed in the article has allowed us to compare the mechanisms of stimulating citizens to achieve the level of self-sufficiency and highlight key features and differences. The activities of foreign programmes encourage population to actively integrate into the labour market while providing assistance in exchange for fulfilling obligations to improve their skills, find a job, ensure financial security and opportunities for professional growth and self-sufficiency in the future. The programmes are not only successful in the social protection system, but also reduce poverty and inequality. The article shows that the domestic experience of implementing social support for citizens through the social contract allows us to comprehensively solve the problem of stimulation and targeted work with beneficiaries, forming an independent and informed choice of household members. The expansion of the programme acts as a guideline for continuing state support activities and ensuring interdepartmental interaction in order to form a strategic approach in the development of the state support measures for the family through targeted programmes with an effective combination of direct financial assistance and incentive measures for the long term.